Remembering Wai-Horotiu: microhistory, public art, and Indigenous environmental justice in Tāmaki Makaurau - Meg Parsons (Kōtuitui)
Few people walking along Queen Street in Tāmaki Makaurau Auckland, realise they are treading above Wai-Horotiu, a historically significant stream now buried beneath the urban landscape. In this paper, I examine how Wai-Horotiu, once vital to the socio-cultural and ecological well-being of mana whenua, was systematically canalised, polluted, and ultimately hidden underground through settler colonial interventions. Drawing on settler colonial theory and Indigenous environmental justice frameworks, I adopt a microhistory approach to reveal how these processes deliberately disrupted Māori relationships with their ancestral waterscapes and resulted in enduring ecological and social impacts. The story of Wai-Horotiu illustrates broader patterns of ecological and cultural erasure characteristic of colonial water governance practices, both locally and globally. Additionally, I explore recent artistic and nature-based restoration efforts, including stream daylighting initiatives, which actively challenge colonial narratives, reaffirm Māori presence, and provide hopeful pathways toward restoring reciprocal tangata-wai (people-water) relationships and achieving environmental justice in contemporary urban spaces.